The sable quean eaudiobook - Jacques, Brian (Redwall, 2010)
Vilaya the Sable Quean, her henchman Zwilt the Shade, and their savage cronies have set their sights on Redwall Abbey. Spiriting away one unlucky Redwall youngster after another, the vermin hope to weaken the abbey's resolve and soften it for a takeover. But what Vilaya and Zwilt don't know is someone else is headed toward the abbey. Buckler, Blademaster of the Long Patrol, is among the bravest hares ever to set foot in Mossflower Wood. A hero-in-waiting, he is perfectly suited to strike down the evildoers.